Objectively Measured Physical Activity Predicts Hip and Spine Bone Mineral Content in Children and Adolescents Ages 5–15 Years: Iowa Bone Development Study - Janz, Kathleen F.; Letuchy, Elena M.; Francis, Shelby L.; Metcalf, Kristen M.; Burns, Trudy L.; Levy, Steven M. (Frontiers in Endocrinology, 2014)
This study examined the association between physical activity (PA) and bone mineral content (BMC; g) from middle childhood to middle adolescence and compared the impact of vigorous-intensity PA (VPA) over moderate- to vigorous-intensity PA (MVPA). Participants from the Iowa Bone Development Study were examined at ages 5, 8, 11, 13, and 15 yr (n=369, 449, 452, 410, 307, respectively). MVPA and VPA (min/day) were measured using ActiGraph accelerometers. Anthropometry was used to measure body size and somatic maturity. Spine BMC and hip BMC were measured via dual-energy x-ray absorptiometry. Sex-specific multi-level linear models were fit for spine BMC and hip BMC, adjusted for weight (kg), height (cm), linear age (yr), non-linear age (yr2), and maturity (pre peak height velocity vs. at/post peak height velocity). The interaction effects of PA×maturity and PA×age were tested. We also examined differences in spine BMC and hip BMC between the least (10th percentile) and most (90th percentile) active participants at each examination period. Results indicated that PA added to prediction of BMC throughout the 10-year follow-up, except MVPA did not predict spine BMC in females. Maturity and age did not modify the PA effect for males nor females. At age 5, the males at the 90th percentile for VPA had 8.5% more hip BMC than males in the 10th percentile for VPA. At age 15, this difference was 2.0%. Females at age 5 in the 90th percentile for VPA had 6.1% more hip BMC than those in the 10th percentile for VPA. The age 15 difference was 1.8%. VPA was associated with BMC at weight-bearing skeletal sites from childhood to adolescence, and the effect was not modified by maturity or age. Our findings indicate the importance of early and sustained interventions that focus on VPA. Approaches focused on MVPA may be inadequate for optimal bone health, particularly for females.